Awareness of cord blood collection and the impact on banking. Issue 7 (23rd January 2017) - Bhandari, Rusha; Lindley, Amy; Bhatla, Deepika; Babic, Aleksandar; Mueckl, Kathy; Rao, Rakesh; Brooks, Paula; Geiler, Vicki; Gross, Gilad; Al‐Hosni, Mohamad; Shenoy, Shalini
Abstract: Background: Umbilical cord blood (UCB) is an important source of hematopoietic stem cells for transplantation especially in minority populations with limited chances of finding a histocompatible volunteer donor in the registry. UCB has the advantages of early availability, successful outcomes despite some histocompatibility mismatch, and low incidence of chronic graft‐versus‐host disease. Public cord blood banks that disseminate UCB products for transplant depend on voluntary donation at participating hospitals and obstetrical providers for collection. Procedure: Using survey questionnaires, we evaluated attitudes toward UCB donation, the frequency of donation, and provider opinions on UCB collection in the greater St. Louis metropolitan area that caters to minority ethnicities in significant numbers. Results: Our data suggest that nervousness and lack of information regarding the donation and utility of the product were ubiquitous reasons for not donating. Additionally, irrespective of age or level of education, women relied on healthcare providers for information regarding UCB donation. Providers reported primarily time constraints to discussing UCB donation at prenatal visits (54%). Of the interviewees, 62% donated UCB. Fallout due to refusal or preferring private banking was miniscule. Conclusions: These results suggest that dedicated personnel focused on disseminating information, obtaining consent, and collecting the UCB product at major hospitals can enrich cord blood banks especially with minority cords. Sustained and focused efforts could improve upon a relatively high wastage rate and ensure a robust supply of UCB products at local public banks.